ETHICS AND LOGIC ANALYSIS IN THE DEVELOPMENT OF SCIENCE, TECHNOLOGY, AND ARTS - Mokhamad Yaurizqika Hadi (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2022)
This article was written to explore the relationship between ethics, logic and art and science. The results of this article show that science is unlimited and in its use it should always be based on ethics which serves to contribute considerations about the good and bad, right and wrong of the use of science. Then between logic, ethics and art become an inseparable part of the development of science. This research uses a literature study method by looking for various sources of data from books, journal articles, proceedings and relevant seminars. Search for literature sources by utilizing the Google Schoolar database, the Garuda Publication Indonesia Index (IPI) Portal, nationally accredited journals (SINTA), Google Books, Printed Books and other reference sources.